The Role of Characters in in Characterization the Alienated Hero between the two Collections of “Death of Bed No. 12” by Ghassan Kanafani and “My Little Chapel” by Hushang Golshiri (Journal of Human Sciences, 2026)
Characters are the most prominent components of a literary work, as the rest of the elements work together to form and build characters, which is called characterization. Perhaps one of the distinctive methods of characterization is to draw characters through other characters, that is, characterizing them through other characters’ vision of them or their vision of them in a way that reflects their interior, thought, and principles, which is what we were interested in in this research. According to the comparative, we studied and compared the characterization of the expatriate hero through other characters in two short story collections, which are: “Death in Bed No. 12” by the Palestinian author Ghassan Kanafani, and “My Little Prayer Room” by the Iranian author Houshang Golshiri. The research concluded that the hero’s view of the other characters, his opinion of them, and his comments on their words or actions reflected the depth of his alienation, which was often manifested in helplessness and isolation among Kanafani’s heroes, and fear, a tendency to withdraw from the crowd, lack of trust in others, and helplessness among Golshiri’s heroes. This revealed the flaws of both societies: the Arab society's refusal to accept ordinary people as substitutes for revolutionary heroes, which created alienated heroes, and the Persian society's inability to integrate its people, among other outcomes that we will discuss later.